Review (article) of Wim Vandenbussche, Ernst Håkon Jahr and Peter Trudgill (eds.). Language Ecology for the 21st Century: Linguistic Conflicts and Social Environments. Oslo, Norway: Novus Press. 2013. - Ansaldo, Umberto (WILEY-BLACKWELL, 2015)
BOOK REVIEW